Opis, analiza in vrednotenje teorije medosebnih odnosov Hildegard E. Peplau v pediatrični zdravstveni negi - Cilar, Leona (Obzornik zdravstvene nege, 2020)
Introduction: The basic characteristics of pediatric nursing include the best possible care for the child, the maintenance of family integrity and the child's routine, as well as the special knowledge and skills needed for the care of a child. The theory of interpersonal relations emphasizes the importance of interpersonal relations between a nurse and a patient, which develops through phases of interpersonal relations. The aim of the description, analysis and evaluation of the theory is to determine the possibility of transferring and using the theory in the practice of pediatric nursing. Methods: A review of the scientific and professional literature was used in the following databases: Web of Science, ProQuest, Medline, PubMed, ScienceDirect and CINAHL. PRISMA recommendations were considered. We ranked the identified search hits according to the hierarchy of evidence, and evaluated the quality of the study using the GRADE recommendations. The theory was described, analyzed and evaluated according to Pajnkihar's model. Results: Of the 321 identified hits, 21 were included in the final analysis. Through the analysis of the identified hits, we have found that most authors define the theory of interpersonal relations as medium-range theory. They also generally agree that the theory is simple as well as complex, and has clearly described concepts, propositions and assumptions. The phenomenon of interpersonal relations is clear to nurses in a clinical setting. Discussion and conclusion: The theory is useful for nursing practice, research, and education. Testing the theory in pediatric nursing is required before applying the theory in practice and education. The theory supports the development of interpersonal relations, as well as verbal and non-verbal communication and may be used in theory-based practice.
Keywords: interpersonal relationships; medosebni odnosi; nursing care; nursing theory; pediatric nursing; pediatrična zdravstvena nega; Peplau, Hildegard; teorije; theories; zdravstvena nega